BPDAC: A Blockchain Based and Provenance Enabled Dynamic Access Control Scheme - Lianshan Sun; Danni Zhou; Diandong Liu; Jingyan Tang; Yang Li (IEEE Access)
Access control is a widely used technology for securing sensitive resources of information systems, ranging from personal data managed by cloud-based data stores to sensitive data stream collected by smart devices. Existing access control systems mainly adopt centralized architecture and static access control models, including Access Control List, Role-based Access Control and Attribute-based Access Control. However, these systems fail to meet the increasing requirements of behavior based dynamic access control or requirements of owner initiated autonomous access control without relying on trustworthy third parties and suffer inherent drawbacks of a single point of failure or dishonesty. To this end, a novel blockchain-based and provenance enabled dynamic access control scheme called BPDAC is proposed. Specifically, it collects and stores data provenance on blockchain to enable behavior-based dynamic access control; in particular, the quick lookup table (QLT) structure is designed to speed up access control evaluation based on provenance with increasing complexity. It also provides specifications for formulating access control policy based on provenance. It utilizes a set of smart contracts on blockchain to enable decentralized and reliable autonomous access control. A prototype system is implemented on the Hyperledger Fabric and experiments are conducted to show that the proposed scheme is practically feasible and scalable in terms of the performance metrics of throughput and latency.